2020
DOI: 10.1111/aor.13671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of turbulent blood flow in the aortic root on de novo aortic insufficiency during continuous‐flow left ventricular‐assist device support

Abstract: Mechanical circulatory support with a continuous-flow left ventricular-assist device (LVAD) is a well-established procedure as a bridge to transplantation, and long-term LVAD support has become more important not only as a bridge to transplantation but also as a destination therapy along with improvements in device durability. 1 Aortic insufficiency (AI), while on LVAD, affects 25%-30%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…[9][10][11] Few reports are available regarding the clinical implications of LVAD--not only Jarvik 2000--outflow-graft anastomotic site and they mostly refer to single center experience with varying results. [12][13][14] However, no clinical studies have been reported to date for comparison of ascending versus descending aortic anastomosis in Jarvik 2000. Our unique multicenter series revealed that the site of outflow graft anastomosis to the ascending aorta is safe and technically feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Few reports are available regarding the clinical implications of LVAD--not only Jarvik 2000--outflow-graft anastomotic site and they mostly refer to single center experience with varying results. [12][13][14] However, no clinical studies have been reported to date for comparison of ascending versus descending aortic anastomosis in Jarvik 2000. Our unique multicenter series revealed that the site of outflow graft anastomosis to the ascending aorta is safe and technically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Jarvik 2000 LVAD is a widely used device and it was originally conceived for left thoracotomy implantation on beating‐heart through anastomosis onto the descending aorta 9‐11 . Few reports are available regarding the clinical implications of LVAD––not only Jarvik 2000––outflow‐graft anastomotic site and they mostly refer to single center experience with varying results 12‐14 . However, no clinical studies have been reported to date for comparison of ascending versus descending aortic anastomosis in Jarvik 2000.…”
Section: Discussionmentioning
confidence: 99%
“…CFD is necessary to obtain the local distribution of some key parameters such as WSS, velocity vectors, etc. A few CFD studies combining the aorta and LVADs were based on the long-term, durable, and surgically-implanted LVADs (Mazzitelli et al, 2016 ; Yoshida et al, 2020 ), which have different outlets and outflows compared with short-term percutaneously inserted devices. Furthermore, short-term LVADs are used for patients with different indications compared with durable LVADs.…”
Section: Introductionmentioning
confidence: 99%
“…What we have known for a while is that moderate to severe AI in CF-LVADs portends a worse clinical outcome in terms of heart failure admissions and overall survival. 2 The progression of the AI with the CF-LVAD has been hypothesized to be related to turbulent blood flow in the root, 3 potentially associated with outflow graft location and angle of anastomosis. Recognizing the importance of the influence of moderate to severe AI on CF-LVAD outcomes has led to most addressing the AI by repairing the aortic valve with a central coaptation stitch (ie, Park's stitch) or aortic valve replacement with reasonably equivalent results.…”
mentioning
confidence: 99%